Teachers’ Reading Culture in Madrasah Tsanawiyah Environment of the Target Grant Program of School and Quality Component Assistance - Siahaan, Amiruddin (SCAD Independent, 2017)
The low reading culture in teachers has an impact on the low ability and interest in writing scientific papers, of course; also have an impact on the stagnant level of education and teacher’s rank. Nationally, most of the teacher's rank stops at group IV A. Because starting group IVA and above class increased, it requires the component of writing scientific papers, besides teaching component. The results showed that reading culture among Madrasah teachers who became the object of this research increased after the Grant Program of School Quality Component Assistance 3 Madrasah accreditation phase 2 of Indonesia Education Partnership to Australia. They are increasingly aware of the importance of improving the quality of self and improving the quality of Madrasah. Efforts are made to improve the culture of reading teachers, including 1) adding facilities for reading places, such as libraries and reading parks; 2) increasing the number of books collected in Madrasah, related to subjects and textbooks supporting subjects; 3) involving teachers in scientific forums, such as scientific paper competition, short stories, and seminars; 4). The principal as a leading coach for teachers provides motivation to teachers through teacher board meetings as well as directly, in order to increase interest in reading their teachers.